Alumina fiber-reinforced silica matrix composites with improved mechanical properties prepared by a novel DCC-HVCI method. Issue 18 (15th December 2017) - Xiao, Huan; Wu, Jia-Min; Chen, An-Nan; Liu, Rong-Zhen; Chen, Jing-Yan; Cheng, Li-Jin; Gan, Ke; Shi, Yu-Sheng; Li, Chen-Hui
Abstract: A novel direct coagulation casting via controlled release of high valence counter ions (DCC-HVCI) method was applied to prepare the alumina fiber-reinforced silica matrix composites with improved mechanical properties. In this method, the silica suspension could be rapidly coagulated via controlled release of calcium ions from calcium iodate and pH shift by hydrolysis of glycerol diacetate (GDA) at an elevated temperature. The influence of tetramethylammonium hydroxide (TMAOH) dispersant amount, volume fraction and calcium iodate concentration on the rheological properties of suspensions was investigated. Additionally, the effect of alumina fiber contents on the mechanical properties of alumina fiber-reinforced silica matrix composites was studied systematically. It was found that the stable suspension of 50 vol% solid loading could be prepared by adding 2.5 wt% TMAOH at room temperature. The addition of 0–15 wt% alumina fibers had no obvious effect on the viscosity of the silica suspension. The controlled coagulation of the suspension could be achieved by adding 6.5 g L −1 calcium iodate and 1.0 wt% GDA after treating at 70 °C for 30 min. Compressive strength of green bodies with homogeneous microstructure was in the range of 2.1–3.1 MPa. Due to the fiber pull-out and fracture behaviors, the mechanical properties of alumina fiber-reinforced composites improved remarkably. The flexural strength of the composite with 10 wt% alumina fibers sintered at 1350 °C was about 7 times of that without fibers. The results indicate that this approach could provide a promising route to prepare complex-shaped fiber-reinforced ceramic matrix composites with uniform microstructure and high mechanical properties.